Breast imaging, breast surgery, and cancer genetics in the age of COVID‐19. Issue 20 (4th August 2020) - Yin, Kanhua; Singh, Preeti; Drohan, Brian; Hughes, Kevin S.
Abstract : Background: The objective of the current study was to provide insight into the effect of coronavirus disease 2019 (COVID‐19) on breast cancer screening, breast surgery, and genetics consultations. Methods: User data from a risk assessment company were collected from February 2 to April 11, 2020. The use of risk assessment was used as a proxy for the use of 3 breast cancer services, namely, breast imaging, breast surgery, and genetics consultation. Changes in the use of these services during the study period were analyzed. Results: All 3 services experienced significant declines after the COVID‐19 outbreak. The decline in breast surgery began during the week of March 8, followed by breast imaging and genetics consultation (both of which began during the week of March 15). Breast imaging experienced the most significant reduction, with an average weekly decline of 61.7% and a maximum decline of 94.6%. Breast surgery demonstrated an average weekly decline of 20.5%. When surgical consultation was stratified as breast cancer versus no breast cancer, the decrease among in non–breast cancer patients was more significant than that of patients with breast cancer (a decline of 66.8% vs 11.5% from the pre‐COVID average weekly volume for non–breast cancer patients and patients with breast cancer, respectively). During the week of April 5, use of genetics consultations dropped to 39.9% of the average weekly volumes before COVID‐19. Conclusions: COVID‐19 has had a significant impact on the number of patients undergoing breast cancer prevention, screening, diagnosis, and treatment. Abstract : Coronavirus disease 2019 (COVID‐19) has had a significant impact on the number of patients undergoing breast cancer prevention, screening, diagnosis, and treatment in the United States. In the current study, user data from a risk assessment company were collected from February 2 to April 11, 2020, with the use of risk assessment used as a proxy to analyze changes in the use of 3 breast cancer services: breast imaging, breast surgery, and genetics consultation.